Current diagnosis & treatment : family medicine - South-Paul, Jeannette E.; Matheny, Samuel C.; Lewis, Evelyn L., 1956- (New York : McGraw-Hill, 2020)
An easy-to-use guide to the diagnosis, treatment, and management of the full range of clinical conditions seen in primary care. New content includes coverage of genetics and precision medicine use in family medicine, telehealth in family medicine, CTE and sports injuries, Zika, the opioid epidemic, Hepatitis C, expansion of the HIV section, veteran's health and PTSD, and more. The leading resource for USMLE Step 3 review, board certification and maintenance or recertification. Essential for primary care trainees, practicing physicians, advanced practice nurses, and physician assistants. Features Organized according to the developmental lifespan, beginning with childhood and adolescence and progressing through adulthood and senior years. Features: Evidence-based recommendations, Conservative and pharmacologic therapies, Complementary and alternative therapies when relevant, Suggestions for collaborations with other healthcare providers, Attention to the mental and behavioral health of patients as solitary as well as comorbid conditions, Recognition of impact of illness on the family, Patient education information, End-of-life issues
Section I. Infancy & childhood -- Section II. Physical activity in adolescents -- Section III. Adults -- Section IV. Geriatrics -- Section VI. Psychological disorders
"Lange medical book."
Includes bibliographical references and index
Keywords: Family Practice -- methods(DNLM)D005194Q000379; Diagnosis(DNLM)D003933; Family Practice(DNLM)D005194; Family Health(DNLM)D005192